PENGARUH PRAKTIK KEWIRAUSAHAAN DAN LINGKUNGAN KELUARGA TERHADAP MINAT BERWIRAUSAHA PADA SISWA SMK NEGERI 1 PEKANBARU - Dewi Kurniawati; Sumarno Sumarno; Hardisem Syabrus (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2020)
Abstract: This study aimed to determine the influence of the entrepreneurial practice and the family environment on the entrepreneurial interests of students in SMK Negeri 1 Pekanbaru. The total population in this study were all of the students of class XI SMK Negeri 1 Pekanbaru which is 470 students. This study used the Slovin formula to determine the number of samples which was used from the entire population with an overall level of 10%, so the sample is taken at least, 83 students. Testing the data by using questionnaires and documentation. The data analysis used is multiple linear regressions. The results showed that the entrepreneurial practice and the family environment had a significant influence on the entrepreneurial interests at students in SMK Negeri 1 Pekanbaru, in the amount of 0.178 and 0.065 with the regression equation Y = (-15.993) + 0.178 X1 + 0.065 X2 and contributed 29.4% to the entrepreneurial interests.Key words: The Entrepreneurial Practice, The Family Environment, The Entrepreneurial Interests